Criminal protection as a factor in environmental education in Brazilian society (Research, Society and Development, 2022)
The environment is constituted as a founding idea linked to the very need for survival of humanity itself, and therefore, it presents itself as a form of action with special relevance for any State. In turn, criminal law, as the most intense and incisive arm available to the Public Power in the search for social pacification, must serve not only as a purely repressive mechanism, but also, and in the environmental case more prominently, as a pedagogical factor aimed at the creation of a general awareness that protects the environmental legal asset, helping environmental education. In this way, with the almost conflicting junction of these two branches of knowledge (education and criminal law), we can see the social possibility of a movement, of an essential character, in the consolidation of a feeling of all for the protection of the environment, through behaviors focused on the transversality of environmental education, and thus meeting the ethical-social function of criminal law.